Full-Scale Tests to Failure Compared to Assessments : Three Concrete Bridges - Bagge, Niklas; Nilimaa, Jonny; Puurula, Arto; Täljsten, Björn; Blanksvärd, Thomas; Sas, Gabriel; Elfgren, Lennart; Carolin, Anders (Luleå tekniska universitet, Byggkonstruktion och brand, 2018)
Three Swedish concrete bridges have been tested to failure and the results have been compared to assessment using standard code models and advanced numerical methods. The three tested and assessed bridges were: (1)Lautajokk, a 29 year old one span (7 m) concrete trough bridge tested in fatigue to check the concrete shear capacity. (2)Ӧrnskldsvik, a 50 year old two span trough bridge (12 + 12 m) strengthened to avoid a bending failure. (3)Kiruna Mine Bridge, a 55 year old five span prestressed concrete road bridge (18 + 21 + 23 + 24 + 20 m) tested in shear and bending of the beams and punching of the slab. The main results in the paper are the experiences of the real failure types, the robustness/weakness of the bridges, and the accuracy of different codes and models. In all three cases the bridges had a considerable hidden capacity.